IMPELEMENTASI SISTEM PEMANTAUAN OBJEK BERGERAK DENGAN MEMANFAATKAN FREKUENSI RADIO MENGGUNAKAN GPS (GLOBAL POSITIONING SYSTEM) - Triandi, Budi (Bina Nusantara University, 2010)
GPS was developed by the United States Department of Defense as a reliable means for accurate navigation. The system provides highly accurate position and velocity information and precise time on a continuous global basis to an unlimited number of properly equipped users. By using combined GPS receiver and microcontroller together with radio system, we can design a monitoring system for our vehicles and display the result on the computer. This system consists of a master module that transmits and receives signals from computer and two slave modules to collect GPS data from vehicles. The result of experiment shows that this system is able to track the vehicle on digital map with accuracy as high as 95%.Keywords: GPS, microcontroller, monitoring, RF